FOTOTERAPI 405NM BLUE LIGHT LASER SEBAGAI ALTERNATIF TERAPI GONORE KOINFEKSI KLAMIDIASIS RESISTEN ANTIBIOTIK - Alfiani Zukhruful Fitri; Clara Alverina (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background: Gonorrhea is a sexually transmitted infection (STI) caused by Neisseria gonorrhoeae, which generally attacks genital mucosa. The incidence of gonorrhea is pretty high, WHO mentioned 87 million new cases in 2016. The co-infection with Chlamydia trachomatis is around 10-40%. According to WHO 2018, 70% of countries reported antimicrobial resistance to N. gonorrhoeae. Besides, third-generation cephalosporin resistance has also been found in 10 countries. Method: This literature study aims to determine the potential alternative therapy for antibiotic-resistant gonorrhea with chlamydia co-infection. The source used in this literature comes from scientific journals at Google Scholar, PubMed, and WHO publications from 2015-2020. Discussion: Antimicrobial blue light (aBL) is a type of therapy to control antibiotic-resistant bacterial infections based on the use of light. The mechanism of aBL with a wavelength of 405 nm is by inactivating microbes through cytotoxic and genotoxic effects through endogenous photosensitizers on microbes that cause damage to cell membranes and inactivation of bacterial virulence factors, both N. gonorrhoeae, and C. trachomatis. Conclusion: Phototherapy 405 nm Blue Light Laser can be an alternative non-pharmacological therapy for the treatment of gonorrhea, both single infection and chlamydial coinfection. The advantages, are easy to use, non-invasive, require a fairly short duration, have high selectivity so that it does not harm vaginal epithelial cells, and there is no resistance to this phototherapy.